Fabrication Process and Performance Analysis of CSP LED Filaments with a Stacked Package Design - Nan Jiang; Jun Zou; Changran Zheng; Mingming Shi; Wenbo Li; Yiming Liu; Bin Guo; Jerry Liu; Herry Liu; Xavier Yin (Applied Sciences, 2018)
This article presents a chip-scale package (CSP) based filament light-emitting diodes (LEDs) with a stacked-type structure and a segmented-type luminescence design for higher luminous efficiency and better electrical stability. The innovation strategy improves the luminous efficiency by 7.69% and 18.97% than the traditional dispensing packaged LED filament when the current is at 30 mA and 210 mA, respectively, and reduces the use of red phosphors and green phosphors by 66.7% and 26.2%, respectively. With the increase of the current, the luminous efficiency variations of the stacked-packaged filament are lower than that of the traditional dispensing packaged filament. Moreover, the color temperature of the filament is no longer determined by the calculation of the ratio of various phosphors. The stacked structure and the segmented design can help us to adjust the specified color temperature quickly by changing the proportion and position of the blue chips and the red CSP LEDs.